Mercury removal from incineration flue gas by organic and inorganic adsorbents - Jurng, J; Lee, TG; Lee, GY; Lee, SJ; Kim, BH; Seier, J (PERGAMON-ELSEVIER SCIENCE LTD, 2002)
Experiments were performed to investigate various adsorbents for their mercury removal capabilities from incineration flue gases. Four different materials were tested; Zeolite, Bentonite, activated carbon (AC), and wood char. Real incineration off-gas and in-lab simulated combustion flue gases (N-2 + Hg) were used. Three cylindrical-shaped sorbent columns with 5 cm in diameter and 20 cm in length were used. The gas flow rate was fixed at 660 l/h at all times. Concentrations of NO, CO, O-2, CO2, SO2, H2O, HCl, and mercury were continuously monitored. Mercury removal efficiencies of natural Zeolite and Bentonite were found to be much lower than those of the referenced AC. Amount of Hg removed were 9.2 and 7.4 mug/g of Zeolite and Bentonite, respectively. Removal efficiencies of each layer consisted of inorganic adsorbents were no higher than 7%. No significant improvement was observed with sulfur impregnation onto the inorganic adsorbents. Organic adsorbents (wood char and AC showed much higher mercury removal efficiencies than those of inorganic ones (Zeolite and Bentonite). Mercury removal efficiency of wood char reached over 95% in the first layer, showing almost same effectiveness as AC which currently may be the most effective adsorbents for mercury. Amount of mercury captured by wood char was approximately 0.6 mg/g of wood char, close to the amount captured by AC tested in this study. Hence, wood char, made from the waste woods through a gasification process, should be considered as a possible alternative to relatively expensive AC. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: CHLORIDE VAPORS; PHASE MERCURY; CAPTURE; ADSORPTION; PARTICLES; SORBENTS